The Effect of Regulatory Quality on Foreign Direct Investment (FDI) Inflows in Asia Using Dynamic Panel Data Method: The Initial Stage Policy Response to Covid-19 - Maizura Abd Rashid, Intan; Ahmad Fauzi Wan Husain, Wan; Hanie Abu Samah, Irza; Nurshahrizleen Ramlan, Sayang; Hamzah, Hariri (International Journal of Psychosocial Rehabilitation, 2020)
The shocking worldwide transmission of COVID-19 has encouraged many governments to interfere to avoid the spread of the infection. In Asia, government’ bodies that govern medical devices have taken steps to ease import restrictions and expedite registration processes for needed goods, seeking to ensure that regulations do not block the development or supply of devices that could save lives. A good regulatory quality reflects perceptions of the capability of the regulatory to frame and implement sound policies and regulations that permit and help all sector development. Following the spread of COVID-19 and increased financial volatility, the growth of FDI and trade outlook for the region in 2020 has been sharply downgraded. This research used dynamic panel data, also known as a longitudinal study, and observed data from January 2020 to March 2020 in 5 selected Asian countries involved with COVID-19. This study found the Dynamic Panel Data System GMM Estimation model is fitting to interpret the outcome, indicating the regulatory quality of Covid-19 (p-value=0.036), the inflation rate, and the unemployment rate have a significant relationship in panel analysis amounting to 1% significance, 2% significance, and 5% significance. In terms of limitations, this study just focuses on three months of data from selected Asian countries involved with Covid-19. Panel causality results suggest bidirectional linkages between inward FDI and regulatory quality. Empirical findings suggest that economic policy reforms are required to channelize regulatory quality of COVID-19 to more foreign capital inflows. The governments of Asian countries should pull out policies on FDI inflows and the environment in order to achieve sustainable economic growth and development.